Efficacy and tolerability of low‐dose spironolactone and topical benzoyl peroxide in adult female acne: A randomized, double‐blind, placebo‐controlled trial. Issue 12 (28th August 2020) - Patiyasikunt, Mattana; Chancheewa, Bussabong; Asawanonda, Pravit; Noppakun, Nopadon; Kumtornrut, Chanat
Abstract: Effective therapies for adult female acne (AFA) are limited. Oral spironolactone (SPL), 100–200 mg/day, is currently used off‐label to treat AFA. However, high‐dose SPL results in clinically significant side‐effects which prevent widespread use in clinical practice. The efficacy of low‐dose spironolactone in AFA is unknown. We examined the efficacy and tolerability of low‐dose (25–50 mg/day) oral SPL in Thai women with moderate AFA. A randomized, double‐blind, placebo‐controlled trial was conducted for 12 weeks. Moderate AFA patients aged between 25 and 45 years received a combination of daily topical benzoyl peroxide (BP) 2.5% plus either SPL 25 mg (SPL25 group), SPL 50 mg (SPL50 group) or placebo. We performed total acne counts and Adult Female Acne Scoring Tool (AFAST) grading at 4‐week intervals. The success rate, defined as the proportion of participants achieving a "clear/almost clear" AFAST grade by the end of week 12, was considered as the main outcome. Treatment‐related adverse events (TRAE) were recorded. We enrolled 63 participants in the study. The total acne counts decreased significantly in all three groups ( P < 0.05) as compared with baseline. Participants in the SPL50 group had a significantly higher success rate than those in the placebo group ( P < 0.05). Serum potassium and creatinine levels showed no significant changes with treatment or between groups. A small number of participants in SPL25 and SPL50 reported mild and temporary TRAE, such as menstrual irregularities, breast tenderness and dizziness. The combination of SPL 50 mg/day and topical BP proved effective in improving moderate AFA in Thai women, with an acceptable side‐effect profile. We propose this regimen as an option for treating moderate AFA.